2018
DOI: 10.1159/000486143
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Visceral Fat in the Outcomes of Colorectal Cancer

Abstract: Aim: To determine the relationship of visceral fat (VF) with the surgical outcome of the patients with colorectal cancer (CRC) submitted to curative surgery. Methods: Retrospective analysis of all patients submitted to CRC surgery during 3 years with a minimum of 5 years of follow-up. We assessed the length of hospital stay, complications, pathologic reports, surgical re-interventions and hospital re-admissions, relapses, survival time and disease-free time. VF was calculated based on patients’ pre-operative C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Some authors found that the measurement of visceral fat on CT scan examination is a more sensitive factor than body mass index (BMI) to predict development of anastomotic dehiscence [ 44 , 45 ]. Goulart et al showed a direct relationship between visceral fat and anastomotic leakage and reoperation [ 46 ]. A meta-analysis evaluating visceral fat in patients with laparoscopic colorectal surgery revealed that visceral obesity was associated with longer operative time, less lymph nodes harvested, more conversion to open procedure, higher morbidity, more surgical site infection and more anastomotic leakage [ 47 ].…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…Some authors found that the measurement of visceral fat on CT scan examination is a more sensitive factor than body mass index (BMI) to predict development of anastomotic dehiscence [ 44 , 45 ]. Goulart et al showed a direct relationship between visceral fat and anastomotic leakage and reoperation [ 46 ]. A meta-analysis evaluating visceral fat in patients with laparoscopic colorectal surgery revealed that visceral obesity was associated with longer operative time, less lymph nodes harvested, more conversion to open procedure, higher morbidity, more surgical site infection and more anastomotic leakage [ 47 ].…”
Section: Preoperative Risk Factorsmentioning
confidence: 99%
“…However, most studies have focused on the risk of complications after surgery, rather than recurrence or survival of CRC patients. [13][14][15][16] A few studies have shown the oncologic outcomes of CRC in viscerally obese patients; however, the results and conclusions of such studies vary. Some studies have shown that VO is related to poor progression-free survival and poor response to adjuvant chemotherapy [17][18][19] while other studies have argued that there is no convincing relationship between VO and survival or tumor stage of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A case-matched study 20 has concluded that IIA in patients with obesity (BMI > 30kg/m 2 ) was associated with similar short-term outcomes and lower incidence of incisional hernias, and may possibly reduce the risk of hospital readmission. However, some published studies [21][22][23][24] show that obesity is associated with postoperative complications, anastomotic leakage and re-operation. A negative in uence of visceral fat on lymph nodes harvested was observed in patients with colorectal cancer 22 .…”
Section: Discussionmentioning
confidence: 99%
“…However, some published studies [21][22][23][24] show that obesity is associated with postoperative complications, anastomotic leakage and re-operation. A negative in uence of visceral fat on lymph nodes harvested was observed in patients with colorectal cancer 22 . In our subgroup analysis of patients with BMI ≥ 24 kg/m 2 , there was no signi cant difference found in rate or severity of postoperative complications in the two groups.…”
Section: Discussionmentioning
confidence: 99%